Industrial Applications: New Solutions for the New Era - de Sales Guerra Tsuzuki, Marcos; Pessoa, Marcosiris Amorim de Oliveira; Acácio de Andrade, Alexandre (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book reprints articles from the Special Issue "Industrial Applications: New Solutions for the New Age" published online in the open-access journal Machines (ISSN 2075-1702). This book consists of twelve published articles. This special edition belongs to the "Mechatronic and Intelligent Machines" section.